Firm innovation and generalized trust as a regional resource - Thore Sören Bischoff; Ann Hipp; Petrik Runst (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2022)
Generalized trust within regions represents an important firm resource. We provide empirical evidence on the impact of trust among people in regions on innovation using two distinct data sets. The first one contains firm-level data and is used to analyze how trust affects firm-level innovation in small and medium sized enterprises (SMEs). The second data set is used to analyze the trust-innovation relationship within regions. It allows us to capture innovation in the form of patents and explore spatial patterns. Our observation period ranges from 2004 to 2019. We apply a multilevel approach, panel data models as well as spatial techniques. The results show that generalized trust has a positive impact on a firm's innovativeness, which is particularly strong for small and medium-sized firms and in regions with relatively low levels of trust.
Keywords: D02; D83; O12; O18; O31; 330; Trust; innovation; regional innovation systems; SMEs